2013
DOI: 10.1111/febs.12120
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐like protein MNSFβ covalently binds to Bcl–G and enhances lipopolysaccharide/interferon γ‐induced apoptosis in macrophages

Abstract: Monoclonal non-specific suppressor factor b (MNSFb) is a ubiquitously expressed member of the ubiquitin-like family that is involved in various biological functions. Previous studies have demonstrated that MNSFb covalently binds to intracellular pro-apoptotic protein Bcl-G and regulates the extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK) cascade in the mouse macrophage cell line Raw264.7. In this study, we demonstrate that MNSFb promotes lipopolysaccharide (LPS)/interferon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In particular, the decidual immune cells−predominantly natural‐killer cells and macrophages−preserve a hospitable microenvironment for pregnancy to proceed (Jensen et al, ; Kajihara et al, ), which includes the controlled upregulation of an apoptotic response. Given that MNSFB also regulates apoptosis via its interaction with the proapoptotic proteins BCL‐G and P53 (Pickard et al, ; Siew et al, ; Watanabe et al, ), we suggest that a deficiency in MNSFB levels is responsible for the down‐regulated uterine expression of BCL‐G and P53 (Fig. ).…”
Section: Discussionmentioning
confidence: 68%
“…In particular, the decidual immune cells−predominantly natural‐killer cells and macrophages−preserve a hospitable microenvironment for pregnancy to proceed (Jensen et al, ; Kajihara et al, ), which includes the controlled upregulation of an apoptotic response. Given that MNSFB also regulates apoptosis via its interaction with the proapoptotic proteins BCL‐G and P53 (Pickard et al, ; Siew et al, ; Watanabe et al, ), we suggest that a deficiency in MNSFB levels is responsible for the down‐regulated uterine expression of BCL‐G and P53 (Fig. ).…”
Section: Discussionmentioning
confidence: 68%
“…The killing capacity of endogenous BCL-G was supported by subsequent studies in human osteosarcoma 9 , breast 11 and prostate 12 cancer cell lines, which showed a protective effect of BCL-G depletion during p53 activation or UV irradiation. Other reports, while suggesting a proapoptotic role of BCL-G, lacked a conclusive support for the observed cell death being directly controlled by BCL-G alone 34 . Here, we report that in human IEC and intestinal organoids expression of BCL-G S/L paralleled induction of apoptosis by IFN-γ and TNF-α, where it converged with activation of caspase-9, suggesting engagement of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, we found an increased association between GIT2 and Rpl17 (ribosomal protein L17), Fau/MNSFβ (Monoclonal non-specific suppressor factor β), and Fbxo24 (F-Box Only Protein 24/IKK1) in the pathological db/db state. Interestingly, both Fau/MNSFβ and Fbxo24 are associated with apoptotic activity linked to inflammation and DNA damage ( 108 , 109 ). Proteins commonly co-precipitating with GIT2 in both WT and db/db conditions (Map1a, Pdrg1, Caskin2) were also validated and were found to equally associate with GIT2 in both conditions (Figure 10 D).…”
Section: Resultsmentioning
confidence: 99%